Atmospheric Nanoparticles in Photocatalytic and Thermal Production of Atmospheric Pollutants - R. R. Chianelli; M. J. Yácaman; J. Arenas; F. Aldape (Journal of Hazardous Substance Research, 1998)
Atmospheric aerosols which occur above heavily polluted areas such as Mexico City, are characterized and found to be complex materials that have the potential to accelerate important ozone-forming reactions photocatalytically and thermocatalytically. In addition, because the particles are respirable, they may represent a considerable health hazard. The aerosols consist of two intermixed components. The first component consists of amorphous carbonaceous materials of variable composition with "fullerene like" materials dispersed throughout. The second component is an inorganic material consisting of nanoparticles of oxides and sulfides "supported" on clay minerals. This inorganic component has all of the characteristics of an airborne photocatalyst. Nanoparticles of Fe2O3, MnO2 and FeS2 have demonstrated catalytic properties, particularly when they occur in the nanoparticle range, as they do in the subject aerosol materials. These materials have band-gaps that occur in the broad solar spectrum enhancing the photocatalytic adsorption of solar radiation beyond that of the wider band-gap aluminosilicate and titanate materials, which also occur in aerosols. In addition, the materials are acidic and probably are coated with moisture when suspended in air, further enhancing their catalytic ability to crack hydrocarbons and create free radicals.
Keywords: atmospheric nanoparticles; photocatalyst; atmospheric pollutants